Identification of Temporal Characteristic Networks of Peripheral Blood Changes in Alzheimer’s Disease Based on Weighted Gene Co-expression Network Analysis - Tang, Runhong; Liu, Huayan (Frontiers in Aging Neuroscience, 2019)
Alzheimer's disease (AD) is a progressive neurodegenerative disease. The study of blood-based biomarkers has been lasted for a long time in AD, because it supports the concept that peripheral changes involve in AD pathology. But there is still unclear that how peripheral blood is involved in the temporal characteristic molecular mechanisms of AD from aging to mild cognitive impairment (MCI) to AD and which cells are responsible for the molecular mechanisms. The main purpose of our study is to gain a systematic and comprehensive understanding of temporal characteristic networks of peripheral blood in AD using whole blood samples with 329 case-control samples including 104 control (CTL), 80 MCI who are susceptible to AD, and 145 AD by the weighted gene co-expression network analysis (WGCNA). The module-trait relationships were constructed and validated in independent datasets GSE63061, GSE97760, GSE18309, GSE29378, GSE28146 and GSE29652. Our results indicate that the down-regulated of protein modification and ubiquitin degradation systems and the up-regulated of insulin resistance play a major role in MCI, while the up-regulated of inflammatory cascade dominates in AD, which is mainly mediated by monocytes, macrophages, and microglia. Although there are mixed activation of M1 and M2 macrophages in all stage of AD, the immune neutral state or M2 polarization may predominates in MCI, and M1 polarization may predominates in AD. Moreover, we found that TRPV2, NDUFV1, ATF4, LUC7L3 may mediate the pathological changes in MCI, while SIRPA, LAMP-2, NDUFB5, FPR2 may mediate the conversion from MCI-AD or the pathological changes in AD, which provide a basis for the treatment based on the peripheral blood system. In addition, we also found that the combined diagnosis based on a panel of genes from the red, blue, and brown modules have a moderate diagnostic effect on distinguishing MCI and AD from CTL, suggesting that those panels of genes may be used for detection of MCI and prediction of this conversion from MCI to AD. Our research emphasizes that pathological changes based on temporal characteristics of peripheral blood providing a theoretical basis for targeted peripheral treatment based on appropriate times and identified several panel of genes markers.